Facile and low‐cost production of Lantana camara stalk‐derived porous carbon nanostructures with excellent supercapacitance and adsorption performance. (5th August 2020) - Ganesan, Sivarasan; Eswaran, Muthusankar; Chokkiah, Bavatharani; Dhanusuraman, Ragupathy; Lingassamy, Arul Pragasan; Ponnusamy, Vinoth Kumar; Kumar, Gopalakrishnan; Pugazhendhi, Arivalagan
Summary: In this study, we report a novel biomass‐derived porous carbon nanostructures (BD‐PCNSs) obtained from Lantana camara stem (LAC) using a simple and low‐cost preparation method. LAC biomass was processed with a temperature‐controlled hydrothermal precarbonization cum pyrolysis technique and followed by alkaline surface activation to achieve BD‐PCNSs. The physicochemical properties for the obtained BD‐PCNSs material were confirmed using X‐ray diffraction, scanning electron microscopy, nitrogen sorption isotherms, and X‐ray photoelectron spectroscopy. As‐prepared BD‐PCNSs exhibited excellent performances toward supercapacitance and wastewater treatment. BD‐PCNSs showed high‐specific capacitance ~146 Fg −1 in the aqueous electrolyte with excellent coulombic efficiency, and cyclic retention affirms its green energy storage device fabrication. Also, maximum adsorption capacity (106.4 mg g −1 ) was achieved for the efficient removal of ibuprofen from wastewater and proven as a promising eco‐friendly, and low‐cost absorbent material claim its practical applications. Abstract : Novel Lantana Camara plant biomass‐derived porous carbon nanostructures for the applications towards wastewater treatment as adsorbent material and energy storage as supercapacitor material.